The Current State of Parkinsonism in West Africa: A Systematic Review - Quarshie, J.T.; Mensah, E.N.; Quaye, O.; Aikins, A.R. (Hindawi, 2021)
Parkinsonism is one of the most common neurodegenerative diseases among the elderly. Africa is experiencing an increasing burden of age-related conditions including parkinsonism. However, there is not enough data on the prevalence, symptoms, and management of the disorder in West African patients. )is systematic review examines the current state of parkinsonism in West Africa by discussing its epidemiology, symptomatology, and treatment. We searched PubMed, BioMed Central, and AJOL databases from January 2000 to December 2020 for studies on parkinsonism conducted in West African countries. We included 32 studies in this review: 23 from Nigeria, 5 from Ghana, and 1 each from Benin, Mali, Niger, and Senegal. Out of the 32 reviewed studies, 11 focused on the prevalence of parkinsonism, 4 examined the genetics of Parkinson’s disease (PD), and 17 described the symptomatology and therapy of parkinsonism. )e prevalence of parkinsonism in West Africa ranges from 6.0% to 8.3% of neurologic admissions/consultations. )e estimated crude prevalence of PD in West Africa varies from 15 to 572 per 100,000 people. )us far, no pathogenic genetic variants have been associated with PD in the region. Levodopa is frequently used singly or in combination with other medications to manage parkinsonian symptoms, which is consistent with reports from other African regions. Most of the reviewed studies focused only on PD, limiting assessment of other forms of parkinsonism. Almost all the prevalence studies were hospital-based and monocentric, making it impossible to accurately estimate the true prevalence of parkinsonism in West Africa. Larger community-based prevalence studies are recommended to enable accurate quantification of disease burden. Future genetic investigations should consider a wider array of gene mutations associated with parkinsonism. Moreover, public health surveillance strategies should be established to monitor the epidemiology of the disorder.
Research Article